Differential cellular recognition of antigens during acute Plasmodium falciparum and Plasmodium vivax malaria. - Salwati, E; Minigo, G; Woodberry, T; Piera, K; de Silva, H; Kenangalem, E; Tjitra, E; Coppel, R; Price, R; Anstey, N; Plebanski, M (2011)
BACKGROUND: Plasmodium falciparum and Plasmodium vivax are co-endemic in the Asia-Pacific region. Their capacity to induce and sustain diverse T-cell responses underpins protective immunity. We compared T-cell responses to the largely conserved merozoite surface protein-5 (PfMSP5) during acute and convalescent falciparum and vivax malaria. METHODS: Lymphoproliferation and IFN--γ secretion to PfMSP5 and purified protein derivate were quantified in adults with falciparum (n=34), and vivax malaria (n=12) or asymptomatic residents (n=10) of Papua, Indonesia. Responses were reassessed 7-28 days following treatment. RESULTS: The frequency of IFN-γ responders to PfMSP5 was similar in acute falciparum (63%) or vivax (67%) malaria. However, significantly more IFN-γ-secreting cells were detectable during vivax compared with falciparum infection. Purified protein derivative responses showed a similarly enhanced pattern. While rapidly lost in vivax patients, PfMSP5-specific responses in falciparum malaria remained to day 28. By contrast, frequency and magnitude of lymphoproliferation to PfMSP5 were similar for falciparum and vivax infections. CONCLUSION: Cellular PfMSP5-specific responses are most frequent during either acute falciparum or vivax malaria, indicating functional T-cell responses to conserved antigens. Both effector and central memory T-cell functions are increased. Greater IFN-γ responses in acute P. vivax, suggest enhancement of pre-existing effector T-cells during acute vivax infection.